2018
DOI: 10.3390/ma11050719
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Thermal Behaviour of AA5754-H111 during Fatigue Loading and Fatigue Strength at Fixed Number of Cycles

Abstract: The characterization of the fatigue behaviour of aluminium alloys is still capturing the attention of researchers. As it is well known in literature, for certain alloys, in a specific range of cycles number, the S-N curves do not present any asymptote. So that, problems result in the assessment of the fatigue life. In these conditions, the concept of the fatigue limit has to be replaced by the fatigue strength at a fixed number of loading cycles. Temperature acquisitions during fatigue tests allow for a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For the first block, it is suggested that the maximum stress should be 20%-30% of the ultimate tensile strength of the material to ensure collecting enough data below the fatigue limit. 142 The stress increment between each block can be varied but should be set such that the total test duration remains practical while still collecting a satisfactory number of data points around the fatigue limit. 119 During each block, thermographic acquisitions are performed for a predefined time period and sampling frequency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the first block, it is suggested that the maximum stress should be 20%-30% of the ultimate tensile strength of the material to ensure collecting enough data below the fatigue limit. 142 The stress increment between each block can be varied but should be set such that the total test duration remains practical while still collecting a satisfactory number of data points around the fatigue limit. 119 During each block, thermographic acquisitions are performed for a predefined time period and sampling frequency.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned before, each block includes a specific number of cycles, and after completing each block, the stress is increased until the material fails. For the first block, it is suggested that the maximum stress should be 20%–30% of the ultimate tensile strength of the material to ensure collecting enough data below the fatigue limit 142 . The stress increment between each block can be varied but should be set such that the total test duration remains practical while still collecting a satisfactory number of data points around the fatigue limit 119 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional methods of repairing aluminum alloys, for instance, mechanical fastening, could lead to new defects. Composite patches, unlike traditional methods, do not cause any damage to the parent plate and can be replaced several times [ 1 , 2 , 3 , 4 , 5 , 6 ]. Fiber-reinforced polymer composites are the right choice for being used as a patch since these materials have a high stiffness-to-weight ratio, good fatigue resistance, and excellent corrosion resistance [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accurate assessment of fatigue performance is important for the design and use of engineering structures [1]. In recent decades, a fatigue performance assessment method based on the temperature rise of materials or components under fatigue loading has been developed and applied [2][3][4]. The temperature increase of the material during fatigue comes from the increase of internal energy generated by mechanical work conversion [5,6], which is so-called fatigue self-heating.…”
Section: Introductionmentioning
confidence: 99%